Radiological evaluation of composite bone grafts and ceramic implants in goats - MAITI, S K; SINGH, G R (The Indian Journal of Animal Sciences, 2013)
Radiological observations were performed at days 0, 3D, 60 and 90 post-operatively in different groups of fnwm decalcified allografts and ceramic (ALCAP) implants alone and in combination with autogenous bone marrow and cilralcd plasma in goals. The results demonstrated comparatively faster new bone information in the composite bone grafts and presence of bone matrix is must for utilintion of osteogenic property of bone marrow and citrated plasma.